The Early Reception of Carl Menger's Grundsätze: A Bibliographical Note - Federico Salazar (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Carl Menger's Principles of Economics is one of the pillars of modern economics. It was neither ignored nor disregarded at the time of its publication, as some narratives suggest. Commentaries in journals and newspapers show a broad and auspicious reception, in no way an indifferent one. This new review of the reception examines the first fissures this book caused in classical political economy and the methodology of the social sciences. Menger's book was later recognized as one of the cornerstones of the marginal revolution and the turn to subjective value theory.
Keywords: B13; B31; B41; B53; D46; 330; Carl Menger; Subjectivism; Austrian School; History of Economic Thought